Intervalos entre podas de duas variedades de mandioca - Pereira Moreira, Gabriela Luz; Silveira Viana, Anselmo Eloy; Dias Cardoso, Adriana; Da Silva Santos, Vanderlei; Matsumoto, Sylvana Naomi; Bastos Andrade, Andréa Carla [UNESP] (My University, 2013)
This experiment was conducted to evaluate the effect of pruning interval in two cassava varieties. The experiment was installed in the experimental area of Universidade Estadual do Sudoeste da Bahia, campus of Vitória da Conquista - BA, from December 2008 to July 2010, using a randomized complete block design, with ten treatments and three replications. Treatments were arranged in a 2x5 factorial design, formed by combining two varieties of cassava (Caitité and Sergipe) and five pruning intervals (two, four, six and eight months after planting and a witness - no pruning). The pruning was held at a height of 15 cm from the soil surface. Were evaluated the following characteristics: yields of shoot, root and starch; dry matter content, starch and flour yield. The average varieties were compared by Tukey test and for intervals between pruning, regression analysis. The variety Caitité had higher root yield and higher productivity starch, offsetting the reduction in the dry mass of roots that occurred with the pruning. Pruning negatively influenced most valued characteristics, however, was performed at intervals of every six to eight months, allows better distribution of production shoots, without promoting high reduction in root yield.
Intervals between prunings of two cassava varieties
Keywords: Manihot esculenta Crantz; Starch; Tuberous root